Elections in Kenya: When All Roads in East Africa Lead to Nairobi - Francis, Luangisa (Journal of Public Policy and Administration, 2022)
Kenya went to the elections in August 2022. The increasing unpredictable and competitive elections have often down-graded general election trends in the East Africa region where predetermined outcomes and poll fixing are the often norm Kenya was not going to be an exception. However, the case in Kenya was different this time. The era of unquestionable linchpins in Kenyan politics seemed to no longer dictate the tone among Kenyan voters. The voting alliance usually set among ethnic lines appeared to have been a matter of the past. Leading candidates set tone by disowning violence and instead appealed for peace to their supporters during the process of elections. Independent monitoring via parallel vote tabulations and public access of data released by the electoral commission from polling stations kept the public informed of the contest. Before the elections, during and after, anxiety was on the rise within Kenya, among Kenya's neighbors, the rest of Africa and elsewhere. This study examines the 2022 General Election in Kenya as to the maturity of the Kenya electorate against all the odds that has always beset the nation during such particular times. The example set is worth emulation by willing neighboring East African and African states in particular and the world at large. Literature on the elections from reliable daily and weekly tabloids, newsreels, interviews from the mass media, one- to- one debates with political analysts, active participation in panel discussions on the election and discussion groups furnished the necessary information to put something on paper. The general consensus in the discussion groups pitted Kenya to have made a leap forward. The conclusion can be drawn that a significant progress has been made in Kenya's election process since 2007-2008. The process in 2022 has displayed a maturity of democracy worth rivalling.